Development of HPDC Advanced Dies by Casting with Reinforced Tool Steels. (9th February 2015) - Vicario, I.; Idoiaga, J. K.; Arratibel, E.; Erauskin, I.; Plaza, L. M.; Crespo, I.; Caballero, P.
Abstract : High pressure die casting (HPDC) dies are nowadays manufactured with high quality forged steels. Cavities are made by electrical discharge machining (EDM) or by high speed milling. The average life of an aluminium HPDC die is about 125.000 injections. Refrigeration circuits have simple configurations, because they are produced by drilling the die with straight holes. They are limitations in the distances and diameters of holes. Sensors are placed where the geometry of the die permits an easy machining. In order to obtain complex figures, several rapid prototyping methods have been developed. However, there is a limitation in the life of the dies produced by this technique, from several parts to thousands. A new method to obtain semifinished high pressure die casting dies in a steel of higher mechanical properties and with the refrigeration circuits and sensors embedded into it is described in this paper. The method consists in producing a molten steel alloy with micro-nano-special ceramic particles inserted in it and casting the composite material in sand moulds of the desired geometry. The resultant solidified near-net shape die with the cooling tubes and sensors embedded into it. A use-life and a productivity about 50% and 10% higher are obtained.